1996
DOI: 10.1074/jbc.271.42.26105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Substrate Specificity of the RuvC Holliday Junction Resolvase with Synthetic Holliday Junctions

Abstract: The Escherichia coli RuvC protein endonucleolytically resolves Holliday junctions, which are formed as intermediates during genetic recombination and recombination repair. Previous studies using model Holliday junctions suggested that a certain size of central core of homology and a specific sequence in the junction were required for efficient cleavage by RuvC, although not for binding. To determine the minimum length of sequence homology required for RuvC cleavage, we made a series of synthetic Holliday junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 18 publications
3
55
0
Order By: Relevance
“…In the CPV resolvase model, the ␣2 helix is shorter, and the enzyme can only contact the sugar- phosphate backbone at the junction center. These observations are consistent with and may explain the relative lack of sequence specificity near the junction branch point for the poxvirus enzymes (12,13), compared with the strong preferences observed for E. coli RuvC (43,44).…”
Section: Resultssupporting
confidence: 78%
“…In the CPV resolvase model, the ␣2 helix is shorter, and the enzyme can only contact the sugar- phosphate backbone at the junction center. These observations are consistent with and may explain the relative lack of sequence specificity near the junction branch point for the poxvirus enzymes (12,13), compared with the strong preferences observed for E. coli RuvC (43,44).…”
Section: Resultssupporting
confidence: 78%
“…We have suggested that RuvC binding involves two modes of DNA binding: structure specific binding to recognize the configuration of the Holliday junction and catalytically competent interactions (Shida et al 1996). It has also been suggested that RuvC binding to the junction induces a junction distortion and disrupts several base pairs at the crossover point (Bennett et al 1993;Bennett & West 1995a).…”
Section: Junction Specific Binding and Catalytically Competent Interamentioning
confidence: 99%
“…Various biochemical approaches using model Holliday junctions have been applied to elucidate the reaction mechanism of the RuvC-mediated resolution. RuvC cleaves the junctions by introducing two symmetrically related nicks in the continuous strands near the crossover point (Dunderdale et al 1991;Iwasaki et al 1991;Bennett & West 1995bShida et al 1996). RuvC preferentially cleaves junctions with certain core DNA sequences containing A:T base pairs at the 3 0 side of T (Shah et al 1994;Shida et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely to be an important characteristic of the interaction between RuvC and its DNA substrate (14,16). (iii) In the presence of metal ions such as Mg 2ϩ and Mn 2ϩ , RuvC resolves the junctions by introducing symmetrical nicks in the continuous (noncrossover) strands (14,15,17), and (iv) cleavage occurs preferentially at the consensus sequence 5Ј-(A/ T)TT2(G/C), where 2 represents a cleavage site close to the crossover point (18,19). Following cleavage, the resolution process is completed by DNA ligase, which rejoins the 5Ј-P and 3Ј-OH termini in the nicked duplex products (13,14).…”
mentioning
confidence: 99%